2015
DOI: 10.1038/bjc.2015.297
|View full text |Cite|
|
Sign up to set email alerts
|

HLA class I is most tightly linked to levels of tapasin compared with other antigen-processing proteins in glioblastoma

Abstract: Background:Tumour cells can evade the immune system by dysregulation of human leukocyte antigens (HLA-I). Low quantity and/or altered quality of HLA-I cell surface expression is the result of either HLA-I alterations or dysregulations of proteins of the antigen-processing machinery (APM). Tapasin is an APM protein dedicated to the maturation of HLA-I and dysregulation of tapasin has been linked to higher malignancy in several different tumours.Methods:We studied the expression of APM components and HLA-I, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Factors limiting the efficacy of T cell-based therapeutic strategies include the low mutational burden of GBM, the limited trafficking of immune cells within the tumor and the highly suppressive nature of the tumor microenvironment (TME) ( Desai et al, 2019 ). Another important mechanism that plays a role in the limited clinical impact of T cell-based immunotherapies is represented by defects in HLA class I and APM component expression and function in GBM ( Facoetti et al, 2005 ; Thuring et al, 2015 ). Downregulation, loss or lack of function of HLA class-I APM components have a negative impact on T cell-mediated recognition and lysis of GBM cells.…”
Section: Immunotherapy Based Strategies For the Treatment Of Gbmmentioning
confidence: 99%
“…Factors limiting the efficacy of T cell-based therapeutic strategies include the low mutational burden of GBM, the limited trafficking of immune cells within the tumor and the highly suppressive nature of the tumor microenvironment (TME) ( Desai et al, 2019 ). Another important mechanism that plays a role in the limited clinical impact of T cell-based immunotherapies is represented by defects in HLA class I and APM component expression and function in GBM ( Facoetti et al, 2005 ; Thuring et al, 2015 ). Downregulation, loss or lack of function of HLA class-I APM components have a negative impact on T cell-mediated recognition and lysis of GBM cells.…”
Section: Immunotherapy Based Strategies For the Treatment Of Gbmmentioning
confidence: 99%
“…12,13,[19][20][21] It is also reported that loss of tapasin is more frequent among the other antigen-processing machinery (APM) components, strongly suggesting its central role in escape from CTL immune surveillance to tumors. 15,22 Impaired CTL responses against tapasin-deficient cells have been well established in mouse models. 8,9 In human cases, loss of tapasin alters the peptide repertoire presented by HLA-B Ã 2705 and results in a decrease in alloreactive CTL responses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some MHC I allotypes like the human leukocyte antigen (HLA) B*44:05 ( 16 ) and the chicken BF2*15:01 molecules ( 19 , 20 ) are relatively efficient at selecting high-affinity peptide cargo in the absence of tapasin. This can be advantageous because the expression of tapasin can be down-regulated, as has been documented with a variety of tumors and which is generally associated with worse prognosis ( 21 24 ) or targeted by pathogen-encoded immune evasion molecules ( 25 , 26 ). Conversely, other allotypes, like HLA-B*44:02 and BF2*19:01, are inefficient at loading peptide cargo in the absence of tapasin.…”
Section: Introductionmentioning
confidence: 99%